Neoadjuvant and Adjuvant Treatments Compared to Concurrent Chemoradiotherapy for Patients With Locally Advanced Cervical Cancer: A Bayesian Network Meta-Analysis - Qiao, Yunfeng; Li, Huijun; Peng, Bing (Frontiers in Oncology, 2022)
Aim This study aimed to identify the most effective treatment mode for locally advanced cervical cancer (LACC) by adopting a network meta-analysis (NMA). Methods Randomized controlled trials about treatments were retrieved from PubMed, Medline and Embase. Odds ratios (OR) of overall survival (OS) and progression-free survival (PFS) were calculated by synthesizing direct and indirect evidence to rank the efficacy of nine treatments. Consistency was assessed by node-splitting method. Begg’s test was performed to evaluate publication bias. The surface under cumulative ranking curve (SUCRA) was also used in this NMA. Results A total of 24 eligible randomized controlled trials with 6,636 patients were included in our NMA. These trials compared a total of nine different regimens: radiotherapy (RT) alone, surgery, RT plus adjuvant chemotherapy (CT), concurrent chemoradiotherapy (CCRT), neoadjuvant CT plus CCRT, CCRT plus adjuvant CT, neoadjuvant CT, RT, CCRT plus surgery. Among those therapeutic modalities, we found that the two interventions with the highest SUCRA for OS and PFS were CCRT and CCRT plus adjuvant CT, respectively. ORs and 95% confidence interval (CI) for the two best strategies were CCRT versus CCRT plus adjuvant CT (OR, 0.84; 95% CI, 0.53–1.31) for OS, CCRT plus adjuvant CT versus CCRT (OR, 0.60; 95% CI, 0.38–0.96) for PFS. Conclusions This NMA supported that CCRT and CCRT plus adjuvant CT are likely to be the most optimal treatments in terms of both OS and PFS for LACC. Future studies should focus on comparing CCRT and CCRT plus adjuvant CT in the treatment of LACC. Systematic Review Registration PROSPERO, CRD42019147920.